Moussorgky Festival, supplemental concert given by Koubitzky, June 2, 1924 - Salle Gaveau (Paris, France)::::::::::::::: (France; Office Mondial de Concerts; Paris, 2020)
Announcement of the Moussorgsky festival on June 2, 1924, in Paris, and of the supplementary concert by Koubitzky. No Beethoven pieces were performed.